Effects of superabsorbent polymers on autogenous shrinkage and microstructure in metakaolin-based cementitious materials - Arthur Aviz Palma e Silva; Valdirene Maria Silva Capuzzo; Eugênia Fonseca da Silva; André Maués Brabo Pereira; Lívia Borba Agostinho (Case Studies in Construction Materials)
The incorporation of superabsorbent polymers (SAPs) and metakaolin in high-strength microconcrete offers a promising strategy to enhance performance while reducing environmental impact through clinker substitution. This study evaluates the feasibility and sustainability of SAP-modified microconcretes by analyzing fresh and hardened-state properties, autogenous shrinkage, and microstructural characteristics. Three microconcrete and paste mixes were investigated: a reference mix and two containing 0.15 % and 0.30 % SAP by cement mass, all with 10 % metakaolin substitution and a constant water/cement ratio without additional curing water. The results demonstrated that SAP effectively mitigated autogenous shrinkage, with MKSAP30 reducing shrinkage by 53 % compared to the reference mix. Microstructural analysis revealed a significant refinement in the pore network, reducing the average pore diameter from 508.76 µm (MKREF) to 214.65 µm (MKSAP30), despite an increase in total porosity. Moreover, SAP-modified mixes exhibited improved hydration efficiency, as evidenced by increased C-S-H formation and calcium hydroxide content in thermogravimetric analysis. The elastic modulus increased by 5.2 % and 13.9 % for MKSAP15 and MKSAP30, respectively, suggesting that enhanced hydration and pozzolanic activity offset the expected mechanical loss due to porosity. These findings highlight the dual benefits of SAP incorporation: improving concrete performance while promoting sustainability. The synergy between SAP and metakaolin enhances durability and mechanical properties, making SAP-modified microconcrete a viable solution for high-performance and environmentally friendly construction applications.